Penanganan Limbah Medis Padat di Puskesmas X - Muhamad Iqbal; Dwi Ragil Febriyanti; Agus Somad Saputra (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
Public Health Centre facilities are integral to the healthcare system, playing a vital role in safeguarding public health at the primary level. These facilities, beyond delivering medical services, generate substantial quantities of medical waste due to various healthcare procedures. The management of medical waste in these centers presents challenges, notably the need for interim storage before third-party collection. Additionally, monthly solid medical waste transportation from all District health centers poses concerns about potential waste accumulation. This study falls into the category of descriptive research, aiming to provide an illustrative snapshot of current solid medical waste management. A survey at Public Health Centre X found that each polyclinic produces an average of 0.49 kg of solid medical waste daily, totaling 76.4 kg per month. Notably, all samples during packaging, transportation, and storage phases failed to meet specified criteria. Similarly, during sorting, the majority (83%) did not meet standards, with only one sample (16.3%) complying. This underscores the pressing need for staff training in medical waste procedures. To elevate medical waste management standards, health centers must integrate policies and regulations into their daily operations. Additionally, improving current facilities, infrastructure, and procedures is paramount to address this issue effectively. In conclusion, Public Health Centre facilities, vital for primary healthcare, grapple with medical waste management challenges. This study underscores the importance of immediate action in staff training and policy integration while investing in facility enhancements to achieve optimal medical waste management.